Menachem Kellner : Jewish universalism - Tirosh-Samuelson, Hava, 1950-; Hughes, Aaron W., 1968- (Library of Contemporary Jewish Philosophers, 2015)
Menachem Kellner is an American-born scholar of Jewish philosophy, an educator, and a public intellectual who lives in Israel. For over three decades he taught at the University of Haifa, where he held the Sir Isaac and Lady Edith Wolfson Chair of Jewish Religious Thought as well as several high-level administrative positions. Currently he teaches Jewish philosophy at Shalem College, Israel's first liberal arts college, which seeks to integrate Western and Jewish texts. Trained in ethics and political philosophy, Kellner specializes in medieval Jewish philosophy, arguing that Maimonides' rationalist universalism should serve as the ideal for contemporary Jewish life. Creatively fusing Zionism, modern Orthodoxy, and democracy, his vision of Judaism is open to and engaged with the modern world.